Heart rate variability during physical exercise - Leutheuser, H.; Eskofier, B. M. (International Journal of Computer Science in Sport, 2013)
The normal oscillation of the heart rate is called Heart Rate Variability (HRV). HRV parameters change under different conditions like rest, physical exercise, mental stress, and body posture changes. However, results how HRV parameters adapt to physical exercise have been inconsistent. This study investigated how different HRV parameters changed during one hour of running. We used datasets of 295 athletes where each dataset had a total length of about 65 minutes. Data was divided in segments of five minutes and three HRV parameters and one kinematic parameter were calculated for each segment. We applied two different analysis of variance (ANOVA) models to analyze the differences in the means of each segment for every parameter. The two ANOVA models were univariate ANOVA with repeated measures and multivariate ANOVA with repeated measures. The obligatory post-hoc procedure consisted of multiple dependent tests with Bonferroni correction. We investigated the last three segments of the parameters in more detail and detected a delay of one minute between varying running speed and measured heart rate. Hence, the circulatory system of our population needed one minute to adapt to a change in running speed. The method we provided can be used to further investigate more HRV parameters.